ANALISIS KEMAMPUAN SCIENTIFIC REASONING SISWA KELAS X SMA NEGERI SE-KECAMATAN TAMPAN PEKANBARU PADA MATERI USAHA DAN ENERGI - Lisa Indah Sari; Zulhelmi Zulhelmi; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The ability of scientific reasoning is an ability needed in physics lessons that is in connecting new concepts. The main purpose of this research is to find out the pattern and level of scientific reasoning ability of students class X of SMA Negeri Tampan District of Pekanbaru in the subject work and energy. In this study the population is 324 class X students from SMA Negeri 12 Pekanbaru dan SMA Negeri 15 Pekanbaru. The sample was taken by cluster random sampling so that a sample of 68 students was obtained. The instrument of this research is a test of scientific reasoning ability developed refer to the the Lawson's Classroom Test of Scientific Reasoning (LCTSR) by Lawson. The scientific reasoning problem used consist of 12 reasoned multiple choice questions which represent 6 indicators of scientific reasoning ability, which included conservation reasoning, proportional reasoning, control of variables, probabilistic reasoning, correlation reasoning, and deductive-hyphotesis reasoning. Data is collected by giving a tes of scientific reasoning ability to the sample. Data analysis ini this study used descriptive analysis with scoring techniques in pairs, which provided an overview of the patterns and levels of students scientific reasoning abilities. The results of this study provide an information that the tenth grade students of Tampan District of Pekanbaru in the subject work and energy have a pettern of reasoning in the concrete operational category with a percentage of 100% and have level of scientific reasoning in the category of very less with average percentage of 11,15%.Key Words: Scientific reasoning, Work and Energy, Descriptive Analysis.